Transforming growth factor-β1 and SMAD signalling pathway in the small airways of smokers and patients with COPD: potential role in driving fibrotic type-2 epithelial mesenchymal transition - Brake, Samuel James; Lu, Wenying; Chia, Collin; Haug, Greg; Larby, Josie; Hardikar, Ashutosh; Singhera, Gurpreet K.; Hackett, Tillie L.; Eapen, Mathew Suji; Sohal, Sukhwinder Singh (Frontiers in Immunology, 2023)
Background: COPD is a common disease characterized by respiratory airflow obstruction. TGF-β1 and SMAD pathway is believed to play a role in COPD pathogenesis by driving epithelial mesenchymal transition (EMT). Methods: We investigated TGF-β1 signalling and pSmad2/3 and Smad7 activity in resected small airway tissue from patients with; normal lung function and a smoking history (NLFS), current smokers and ex-smokers with COPD GOLD stage 1 and 2 (COPD-CS and COPD-ES) and compared these with normal non-smoking controls (NC). Using immunohistochemistry, we measured activity for these markers in the epithelium, basal epithelium, and reticular basement membrane (RBM). Tissue was also stained for EMT markers E-cadherin, S100A4 and vimentin. Results: The Staining of pSMAD2/3 was significantly increased in the epithelium, and RBM of all COPD groups compared to NC (p <0.0005). There was a less significant increase in COPD-ES basal cell numbers compared to NC (p= 0.02). SMAD7 staining showed a similar pattern (p <0.0001). All COPD group levels of TGF-β1 in the epithelium, basal cells, and RBM cells were significantly lower than NC (p <0.0001). Ratio analysis showed a disproportionate increase in SMAD7 levels compared to pSMAD2/3 in NLFS, COPD-CS and COPD-ES. pSMAD negatively correlated with small airway calibre (FEF25–75%; p= 0.03 r= -0.36). EMT markers were active in the small airway epithelium of all the pathological groups compared to patients with COPD. Conclusion: Activation of the SMAD pathway via pSMAD2/3 is triggered by smoking and active in patients with mild to moderate COPD. These changes correlated to decline in lung function. Activation of the SMADs in the small airways is independent of TGF-β1, suggesting factors other than TGF-β1 are driving these pathways. These factors may have implications for small airway pathology in smokers and COPD through the process of EMT, however more mechanistic work is needed to prove these correlations.